Criminal justice implications of the macho personality constellation - Zaitchik, Matt C. (Criminal justice and behavior, 1993)
This article outlines a script theory of macho personality and discusses its potential forensic application in the understanding of criminal behavior, the prediction of future dangerousness, and the treatment of male offenders. The macho personality constellation consists of the view of violence as manly, the view of danger as exciting, callous sexuality toward women, and toughness as self-control. Research using the Hypermasculinity Inventory, developed to operationalize the macho personality construct, indicates that macho men are more likely to act violently toward other men, to act violently and callously toward women, and to seek out dangerous situations. Potential areas of criminal justice application include substance abuse, rape and sexual assault, sexual harassment, gang violence, "lust" murders, and abuse of women and children in general